PREVALANCE OF THYROID DISORDER IN 1ST TRIMESTER OF PREGNANCY AND IT'S FETOMATERNAL OUTCOME - Dr. Radhika Parmar, Dr. Hiral Dobariya, Dr. Tulsi Patel, Dr. Kishor Chauhan, (Chelonian Research Foundation, 2023)
Thyroid Dysfunction is defined as alteration in TSH, FT3, FT4 level in pregnancy which may lead to significant Maternal and Fetal complications. and Co-Morbidity. In our country prevalence of Thyroid Dysfunction in different regions is high. Early detection and prompt treatment leads to decrease in Maternal and Fetal complications and Co-Morbidity. AIMS: To study the prevalence of thyroid disorder in 1" trimester of pregnancy and fetomaternal outcome in cases. OBJECTIVES: To study prevalence of subclinical and overt hypothyroidism in 1" trimester of pregnancy. To study prevalence of subclinical and overt hyperthyroidism in 1" trimester of pregnancy. To find out the percentage of controls having a normal thyroid profile. To assess the incidence of obstetrical complications in cases. To assess the incidence of fetal complications in cases. METHODOLOGY: The present study was carried out in department of obstetrics and gynecology in Dhiraj hospital, during the period of 1.5 years from December 2018 to June 2020. SOURCE OF DATA: Antenatal cases coming to OPD in 1" trimester and fulfilling inclusion and exclusion criteria were included in source for study. RESULTS: Prevalence of Thyroid Dysfunction in Pregnancy was High (11.88%) in which Subclinical hypothyroidism was 9.31%, Overt hypothyroidism was 1.98% and Hyperthyroidism was 0.59%. In present study 30.51% of subjects with thyroid disorders and 14.93% of euthyroid subjects had abnormal fetal outcome. 39.66% of the subjects with thyroid and 19.46% of euthyroid subjects had NICU admissions. 56.90% of subjects with thyroid disorders and 32.81% of euthyroid subjects had abnormal maternal outcome. CONCLUSION: Thyroid disorders affect pregnancy world over. In India prevalence of thyroid disorder is higher than western countries. In central Gujarat subclinical hypothyroidism was observed in 9.31% of cases. However other forms of disorders were also noted. Subclinical and overt thyroid disorders were associated with adverse outcome for both mother and fetus. Further work in this field will strengthen the management in specific conditions.